The tourism industry of Guimabal, Miagao, and San Joaquin, Southern Iloilo, Panany, Philippines. - Tatud, Amie Claire G.
The tourism Industry is one of the most vital industries in the Philippines because of effects that it brings about to the country. The government recognizes this importance and works hand in hand with the private stakeholders to further improve and preserve these tourist sites., This study aimed to provide information on tourism in Southern Iloilo by focusing on the three municipalities, namely, Guimbal, Miagao and San Joaquin which perform well in tourism. The information was gathered from the different municipal tourism offices, the Department of Tourism Region VI and is further complimented by facts given by the private stakeholders of the said industry. The efforts of both stakeholders and the effects of tourism are given focus. The effects in particular should be given attention to further improve them and work on those that might present a threat in the near future.